Community based universal neonatal hearing screening by health visitors using otoacoustic emissions. Issue 3 (1st May 2001) - Owen, M; Webb, M; Evans, K
Abstract : OBJECTIVES: To carry out a pilot study to test the feasibility of health visitors (HVs) performing neonatal otoacoustic emissions (OAE) hearing screening in the community using Echoport ILO288 and to evaluate its acceptability to parents and HVs. DESIGN: Prospective cohort study. SETTING: Local health centres and babies' homes in urban and rural settings in West Gloucestershire. PARTICIPANTS: Twelve HVs, 683 babies, and their parents. MAIN OUTCOME MEASURES: Coverage rate, age at testing, referral rate for formal audiology testing, and parental anxiety scores. RESULTS: Of the 683 babies registered with the study HVs, 99% (675) were tested, with a median age at first test of 18 days. Parental consent for the study was refused for six of the eight not tested. Taking a unilateral pass as a screening pass (for comparison with other studies), 4% (27/675) failed the first OAE test, and 1.9% (13/675) failed a second OAE test performed by the HV within a further two weeks and were referred for formal audiology testing. One baby (0.15%) was found to have a moderate sensorineural hearing loss on brain stem auditory evoked responses, giving a false positive rate of 1.7% (12/675). Some 18% (120/675) were tested at home, of which 80% (96/120) were combined with another planned reason for HV contact. In all, 82% (555/675) of tests were carried out in health centre clinics, of which 47% (260/555) were combined purpose visits. Mean parental anxiety scores (possible range 0–5) were 0.86, 2.27, and 3.45 before the first test, first retest, and audiology test respectively. The median time taken for one HV to complete testing was 12.2 minutes (range 3–65), compared with the 15 minutes currently allocated for two HVs to perform distraction testing. Based on the results of questionnaires, the test was very well received by parents and HVs alike. CONCLUSION: HVs are able to perform OAE testing in the neonatal period at home and in local health centre clinics. They achieve high population coverage rates and low false positive rates. Universal neonatal hearing screening by HVs using OAE testing is feasible, well received, and could be less demanding of HV time than the current distraction testing. This model of universal neonatal hearing screening should be considered by the National Screening Committee.